Combinations of bleeding and ischemic risk and their association with clinical outcomes in acute coronary syndrome. (1st September 2019) - Mohamed, Mohamed O.; Kinnaird, Tim; Anderson, Richard; Rashid, Muhammad; Martin, Glen P.; Freeman, Phillip; Kwok, Chun Shing; Myint, Phyo K.; Zaman, Azfar G.; Mamas, Mamas A.
Abstract: Background: Clinical predictors of future ischemic events in patients with acute coronary syndrome (ACS) are also risk factors for bleeding, with patients often at high-risk of both outcomes. We aimed to define the clinical outcomes and provision of guideline-recommended care in ACS management for different combinations of ischemic and bleeding risk defined using a combined GRACE and CRUSADE score. Methods: A retrospective observational analysis of a national ACS database was performed for patients with ACS admitted to three tertiary centres from January 2010 to March 2016. Patients were stratified into 9 groups based on possible CRUSADE-GRACE risk combinations. Multiple logistic regression was used to estimate adjusted odds ratios (ORs [95% CI]) for outcomes (in-hospital net adverse cardiac events (NACE), in-hospital all-cause mortality, 30-day mortality and treatment strategy). Results: A total of 17, 701 patients were included in the analysis. We observed a graded risk of mortality and adverse events in the high-risk GRACE strata (Groups 3, 6 and 9). Almost a third of patients with ACS were at a 'dual high-risk' (Group 9, 32%) and were independently associated with higher in-hospital NACE (composite of cardiac mortality, all-cause bleeding and re-infarction): aOR 6.33 [3.55, 11.29], all-cause mortality: aOR 14.17 [5.27, 38.1], all-cause bleeding: aOR 4.82 [1.96, 11.86], and 30-day mortality: aOR 10.79 [5.33, 21.81]. This group was also the least likely to be offered coronary angiography (aOR 0.24 [0.20, 0.29]) and dual anti-platelet therapy (aOR 0.26 [0.20, 0.34]). Conclusions: One in five patients presenting with an ACS are high ischemic and high bleeding risk, and these patients are more likely to experience poor clinical outcomes and reduced odds of receiving guideline-recommended therapy. Highlights: Combined bleeding-ischemic risk assessment demonstrates that one in three ACS patients are at a 'dual high-risk' of both events. 'Dual high-risk' bleeding-ischemic groups are at greater risk of adverse outcomes and yet less likely to receive guideline-based therapy. Further work is required to identify alternative management strategies that would improve the outcomes of 'dual high-risk' patients.